Praktik Kremasi dalam Gereja Katolik - Bonaventura Farneubun (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2022)
Cremation has been practiced for many reasons over the centuries. Religious purposes, purification, and even live recording, are one of the reasons cremations are carried out by many religious groups, sects, cults, cultures, and civilizations. The practice of cremation also continues to grow and today the practice of cremation is increasingly popular among many people in various regions of the world, including the Catholic Church itself. For about fifteen centuries, the practice of cremation was rejected and condemned by the Church. The Church's consistent attitude which strictly forbids the practice of cremation slowly began to show some shifts in the 1960s with the issuance of the Piam et Constantem decree allowing cremation. Nevertheless, the Church still wants to use it as the first and foremost option.